Development of a Model for the Promotion of Women’s Sports in Iraq - Hamad Ismael, Intisar; Moshkelgosha, Elham; Makki Mahmod, Hussein; Khodaparast, Mahboobeh (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The aim of the present study is to develop a model for the promotion of women's sports in Iraq. Methods and Materials: This research is exploratory in nature and follows a qualitative approach, utilizing grounded theory methodology. The participants in this study included faculty members (sports management) from universities, high-level sports officials and policymakers from the Ministry of Youth and Sports, and the Iraqi National Olympic Committee. These individuals were selected through purposive and theoretical sampling for semi-structured interviews. The interviews continued until theoretical saturation was achieved. The data were simultaneously collected and analyzed using the Strauss and Corbin method. Findings: The results showed that, from an initial 215 conceptual codes, 88 final conceptual codes and 20 subcategories emerged. These were structured within six dimensions of the paradigmatic model, including causal conditions (decision-making bodies, distributive justice, technology, individual factors, interpersonal factors), the main phenomenon (women's sports in Iraq), strategies (creating the formal groundwork for promoting participation, promoting a culture of participation, designing a participation system), intervening conditions (structural weaknesses, lack of financial resources, lack of human resources), contextual conditions (social factors, cultural factors, economic factors, media orientation, laws and regulations), and outcomes (social capital, development of women's sports, women's health development). Conclusion: The integration of these categories, based on the relationships between them, forms the paradigmatic model derived from the qualitative research. Achieving this objective will significantly assist the sports managers in Iraq.